Crossroads - Ukraine and the Triumph of Democracy - Tremblay, Paul (Goula, Iryna ; Tremblay, Paul, 2007)
Verzio FF submission Through the eyes of six Ukrainians, this film examines the history and current events of Ukraine as a context for exploring the even deeper question of democracy and what it means to be - or become - an autonomous, free ,and self-governing people. It is an intricately woven story for those who wish to understand and experience its complexity as Ukraianians do on a daily basis.